PENERAPAN SLOWLY RELAXATION EXERCISE PADA PASIEN POST MASTECTOMY DENGAN MASALAH KEPERAWATAN NYERI AKUT - Kharisna, Dendy; Elwina, Nur; Wardah, Wardah; Epriyanti, Lesti (Yayasan Healing and Healthcare Education, 2024)
One of the clinical manifestations caused by mastectomy surgery is pain. Mastectomy wounds cause lymphedema, limited movement of the shoulder joint, and acute pain. One of the complementary therapies to reduce pain is slow relaxation exercise. The aim of implementing this slow relaxation exercise is to prevent limitations in the range of motion of the shoulder joint and post-operative pain. Exercise applies simple movements that function to improve blood circulation after surgery, facilitate the release of residual surgical blood into the drain tube and make the patient relax. The implementation of KIAN was carried out in the Dahlia Room from June 1 2024 to June 3 2024, carried out at 14.00 with a duration of 5 minutes with a sample of 1 patient. This slow relaxation exercise is carried out on the first post-mastectomy day of surgery. The application of slow relaxation exercise is in the form of physical movements. This exercise is carried out accompanied by a nurse, then the patient can do the exercise independently. The instrument for assessing the pain scale uses VAS (Visual Analogy Scale). The results of this intervention showed a reduction in pain in post-mastectomy patients during 3 days of exercise. The assessment of the pain scale before the slow relaxation exercise was carried out on the first day was 7, on the third day after the slow relaxation exercise was applied the pain scale dropped to 4.